Analisis Faktor Penyebab Kumuh Permukiman Kumuh di Kelurahan Baru Ulu, Kota Balikpapan - Risnayanti Arung; Mega Ulimaz (Jurnal Pembangunan Wilayah dan Kota, 2021)
Slum settlements are one of the problems faced by almost all cities in Indonesia and even other developing countries. UU No. 1 of 2011(1) defines slum settlements as settlements that are unfit for habitation due to building irregularities, high building density levels, and the quality of buildings and facilities and infrastructure that do not meet the requirements. The problem that can be caused is creating inadequate settlements to support the survival of its inhabitants, resulting in a decrease in the welfare, quality and quality of life of the community (2). The Balikpapan city government issued a SK Walikota Balikpapan No. 188.45-667 / 2014(3) concerning the Determination of the Location of Slum Housing and Slum Settlements in the City of Balikpapan, there are a total of 282.20 Ha of slum areas spread across 6 urban villages in the city of Balikpapan. One of the areas stipulated in the decree is located in the Keluarahan Baru Ulu(4) , where this settlement is located close to the city center of Balikpapan. In addition, these slum settlements are located along the coast of Balikpapan Bay which has the potential to cause environmental degradation and disrupt the function of transportation facilities for crossing goods and people who are in direct contact with this slum area. As an effort to reduce slum in the settlements, it is necessary to know the causes of the appearance of slums from various potentially influential aspects. Therefore, this study aims to analyze the factors that cause slum in the slum area of Baru Ulu Village by using the content analysis method to analyze the causes of slum in the research location. Through research, it was found that there are 13 factors that affect slum in Baru Ulu based on stakeholder opinion.